2015
DOI: 10.1089/jpm.2014.0325
|View full text |Cite
|
Sign up to set email alerts
|

Care Management by Oncology Nurses To Address Palliative Care Needs: A Pilot Trial To Assess Feasibility, Acceptability, and Perceived Effectiveness of the CONNECT Intervention

Abstract: Background: Specialty palliative care is not accessible for many patients with advanced cancer. There is a need to find alternative palliative care strategies in oncology clinics. Objective: The objective of the study was to assess the feasibility, acceptability, and perceived effectiveness of an oncology nurse-led care management approach to improve primary palliative care. Methods: The study design was a single-arm pilot trial of the Care Management by Oncology Nurses (CONNECT) intervention, in which registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 65 publications
(47 reference statements)
1
45
0
2
Order By: Relevance
“…Advanced cancer was defined by stage (III/IV),35–37 by presence of metastases (bone,38 39 organs/lymph nodes,40 recurrence or progression of cancer33 41 and by life expectancy or prognosis) 42–44. Other criteria included presence of symptoms such as pain,39 45 fatigue,40 anxiety,46 dyspnoea,32 37 or multiple concurrent symptoms,47 functional status scores,32 48–50 type of treatment being received, scheduled to be received or completed (palliative care,51–53 radiotherapy,32 54 chemotherapy55 56 and surgery57 58), timing of advanced cancer diagnosis8 35 and potential for intensive care unit admission 48…”
Section: Resultsmentioning
confidence: 99%
“…Advanced cancer was defined by stage (III/IV),35–37 by presence of metastases (bone,38 39 organs/lymph nodes,40 recurrence or progression of cancer33 41 and by life expectancy or prognosis) 42–44. Other criteria included presence of symptoms such as pain,39 45 fatigue,40 anxiety,46 dyspnoea,32 37 or multiple concurrent symptoms,47 functional status scores,32 48–50 type of treatment being received, scheduled to be received or completed (palliative care,51–53 radiotherapy,32 54 chemotherapy55 56 and surgery57 58), timing of advanced cancer diagnosis8 35 and potential for intensive care unit admission 48…”
Section: Resultsmentioning
confidence: 99%
“…26 Two other nurse-led intervention studies that included late-stage patients resulted in nonsignificant QOL outcomes; symptoms were not reported in either of these studies. 27,28 A recent study by Schenkle's team 29 demonstrated that palliative care management by specialty trained oncology nurses was feasible and acceptable to patients. Their intervention contained similar essential components to ours and showed promise as one approach of integrating early palliative care into comprehensive oncology care.…”
mentioning
confidence: 99%
“…Enrolling caregivers allows measurement of caregiver outcomes and also facilitates follow-up contact with patients who have high morbidity. Based on our pilot work, we expect that the majority of patient participants will be able to identify a caregiver [20]. However, we do not exclude patients unable to identify a caregiver because we expect that this group also has significant palliative care needs.…”
Section: Methodsmentioning
confidence: 99%
“…In prior work, our team developed a primary palliative care intervention called CONNECT ( C are management by O ncology N urses to address supportive care needs) [20]. The CONNECT intervention is led by oncology clinic nurses who receive specialized training and administrative support to provide symptom management and emotional support, engage patients and families in advance care planning, and coordinate appropriate care using evidence-based care management strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation